Pengembangan Media Pembelajaran Upacara Adat Berbasis Android di SMK Panca Bhakti Banjarnegara - Pertiwi, Imelda Dian; Indiatmoko, Bambang; Supriyanto, Teguh (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
Understanding the contents of the exposition text about the traditional mantu is one of the basic competencies contained in the standard content of Javanese language subjects. Students are expected to fulfill completeness in learning traditional mantu ceremonies. This makes students feel bored and lack an understanding of the material well. The purpose of this study is 1) to find out the needs of students and teachers regarding the development of android-based mantu traditional ceremonial learning media, 2) to develop learning media for android-based mantu traditional ceremonies, and 3) to make prototypes for developing traditional ceremonies based on android. This research uses a development (Research and Development) approach. The procedure of this study is 1) analysis of potential and problems, 2) collecting data, 3) product design, 4) design validation/expert testing, and 5) revisions. Data obtained using 1) interview, and 2) questionnaire. The data analysis technique in this study used qualitative descriptive techniques. The results of the validation test for prototypes of traditional ceremonial learning based on Android are appropriate and appropriate for students and teachers. This media is packaged or printed in the form of an android application.